2012
DOI: 10.1007/s00170-012-4423-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characterization for the dielectric electroactive polymer fundamental sheet

Abstract: A study into the appropriateness of characterizing the dynamics of the dielectric electroactive polymer (DEAP) fundamental sheet has been performed. Whereby a model describing the dynamics of the DEAP fundamental sheet is developed, parameters of the models are determined using experimental/simulation results, and verification has been conducted to determine the precision of the dynamic model. The precision for the DEAP sheet-obtained dynamic model could not be verified unless some parameters characterizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The displacement for U = 800 V was 2–3 times of that for U = 400 V. It indicated that there was more time for recovery due to the increased displacement and the divergence of the modelling error due to the longer recovery time. The error can be minimized by picking the natural frequency of the system [ 12 ].…”
Section: Model Predictions and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The displacement for U = 800 V was 2–3 times of that for U = 400 V. It indicated that there was more time for recovery due to the increased displacement and the divergence of the modelling error due to the longer recovery time. The error can be minimized by picking the natural frequency of the system [ 12 ].…”
Section: Model Predictions and Discussionmentioning
confidence: 99%
“…A comparison of the stored-energy approach, energy-balance approach, and Maxwell-stress-tensor approach to derive expressions for the electrically induced stress state in the dielectric material was made [ 11 ]. Based on the material properties of Young’s modulus and damping, Maxwell stress was applied to obtain the governing equations [ 12 ]. The Maxwell-stress-tensor approach was further applied in modelling the response of PVC actuators [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric electro-active polymer (DEAP) materials are a promising actuation technology due to the merits of lightweight, large strain, high energy density, low-noise, and fast response [1,2]. DEAP materials, as a kind of soft electroactive material, are composed of a polymer film sandwiched between two silver metal soft electrodes layers [3]. The working principle of DEAP materials is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The working principle of DEAP materials is shown in Figure 1. It can be simply divided into three steps [3]: (1) a large driving voltage is applied to the silver metal soft electrodes layers to produce a high electric field; (2) the silver metal soft electrodes layers can be regarded as a flat capacitor, a Maxwell stress will be produced by electrostatic forces; (3) the polymer film is extruded under the Maxwell stress to result in actuation. Based on this basic working principle, DEAP materials have been widely applied in high-precision trajectory tracking control as actuators and achieved great potential for applications in bioinspired soft robots filed, including an arm wrestling robot [4], a flying robot [5], and a swimming robot [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, researchers have focussed on the nonlinear dynamic response of DEAs subjected to a com bined DC and AC voltage [39][40][41] and on the effect of visco elasticity on the dynamics of DEAs [42,43]. With reference to their potential use in applications, such as pumps [44], resonators [9,10], vibrotactile displays [45], and acoustic actuators [12], the dynamic analysis of DEAs has been of continued interest [46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%